The observation of an axillary arch during dissection: A case report - Mohammad Ebrahim Astaneh; Fatemeh Rezaei-Tazangi; Mohammad Reza Astaneh; Reza Arefnezhad (Elsevier, 2023)
Background: The axillary arch is a rare axillary abnormality described as a slim muscular slip extending from the latissimus dorsi to the pectoralis major muscles. This arch has been indicated as the main reason for hyper-abduction syndrome and neurovascular compression in the axillary region. Case presentation: During the dissection of the right axillary cavity of a 74-year-old man for medical students, a case of the axillary arch was found, arising from the lateral border of the latissimus dorsi muscle and terminating in the pectoralis major tendon and the fascia covering the coracobrachialis muscle. Conclusion: Since this variation has not been reported in our country so far, this study can help surgeons to have a better understanding of anatomy and the prevalence of this structure. This muscle can be clinically important in axillary surgeries; due to its influences on the brachial plexus and axillary vessels, covering lymph nodes and altering local anatomy.